2009
DOI: 10.1128/aem.00407-09
|View full text |Cite
|
Sign up to set email alerts
|

Monochloramine Disinfection Kinetics of Nitrosomonas europaea by Propidium Monoazide Quantitative PCR and Live/Dead BacLight Methods

Abstract: Monochloramine disinfection kinetics were determined for the pure-culture ammonia-oxidizing bacterium Nitrosomonas europaea (ATCC 19718) by two culture-independent methods, namely, Live/Dead BacLight (LD) and propidium monoazide quantitative PCR (PMA-qPCR). Both methods were first verified with mixtures of heat-killed (nonviable) and non-heat-killed (viable) cells before a series of batch disinfection experiments with stationary-phase cultures (batch grown for 7 days) at pH 8.0, 25°C, and 5, 10, and 20 mg Cl 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
51
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 41 publications
(47 reference statements)
1
51
0
Order By: Relevance
“…However, traditional fecal indicators to monitor recreational water quality are often not associated with health risks in ambient water where nonpoint sources are dominant fecal contributors, and these results suggest a need for alternative indicators of water quality (47). Furthermore, FIB are inadequate to identify the source of fecal pollution because they are observed in both warm-and cold-blooded animal feces (30,35).…”
mentioning
confidence: 88%
“…However, traditional fecal indicators to monitor recreational water quality are often not associated with health risks in ambient water where nonpoint sources are dominant fecal contributors, and these results suggest a need for alternative indicators of water quality (47). Furthermore, FIB are inadequate to identify the source of fecal pollution because they are observed in both warm-and cold-blooded animal feces (30,35).…”
mentioning
confidence: 88%
“…As a first step in exploring possible medium effects on disinfection kinetics, as determined using two culture-independent methods, Live/Dead BacLight (LD) and propidium monoazide quantitative PCR (PMA-qPCR), batch disinfection experiments were conducted with three different phosphate buffer media (PB) (1, 10, and 50 mM Na 2 HPO 4 , pH 8.0) to compare our results with previous research that used 10 mM phosphate-buffered saline (PBS) (10 mM Na 2 HPO 4 and 130 mM NaCl, pH 8) (27) and to serve as a baseline for future experiments with finished drinking water. Ten millimolar PB, 50 mM PB, and 10 mM PBS represent media commonly used in disinfection experiments (see, e.g., references 18, 20, and 22).…”
mentioning
confidence: 98%
“…If the disinfection mechanism is general acid catalyzed or related to products from monochloramine disproportionation (e.g., dichloramine), the disinfection rate may also increase with increasing phosphate concentration. The experimental results were interpreted based on medium differences in ionic strength and phosphate concentration.Nitrosomonas europaea (ATCC 19718; ATCC, Manassas, VA) bacteria were batch grown (25 to 28°C) to stationary phase (7 days) and then harvested and washed in the same medium used in the batch disinfection experiments as described previously (27). N. europaea was studied because of its use in previous monochloramine disinfection research (27).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…If the flow becomes turbulent, microorganisms are transported by eddies in the flow. Studies have also shown that the type of disinfectant [1,[10][11][12][13], pipe material [10,[14][15][16], hydrodynamics [6,9,12,14,17], availability of nutrients [1,11,[18][19][20][21][22][23][24], and microbial manifestation in the WDS can lead to evident changes in microbial activities. Biofilm development is a result of pioneer attachment, subsequent attachment, and growth of EPS -an essential substance in keeping biofilm organisms together that provides protection against stress, predation, and exposure to a hostile environment.…”
mentioning
confidence: 99%